Learning Curve of Robot-Assisted Thymectomy: Single Surgeon's 7-Year Experience - Meacci, Elisa; Nachira, Dania; Congedo, Maria Teresa; Petracca-Ciavarella, Leonardo; Vita, Maria Letizia; Porziella, Venanzio; Chiappetta, Marco; Lococo, Filippo; Tabacco, Diomira; Triumbari, Elizabeth Katherine Anna; Margaritora, Stefano (Frontiers in Surgery, 2022)
Robotic Assisted Thymectomy (RAT) has rapidly emerged as preferred approach to open transsternal or video-assisted thoracoscopic approach, as a dedicated approach for the treatment of thymoma and non-thymomatous Myastenia Gravis (MG). We aimed to describe and discuss the learning curve (LC) for 113 consecutive RATs performed by the same surgeon. Methods: A single-center retrospective analysis of prospectively-collected clinical data were performed on all patients undergone RAT performed by a single-surgeon from October 2013 to February 2020. The cumulative sum (CUSUM) analysis of the operative time was used to define the completion of our learning curve (CLC) in RAT. The CLC was separately calculated for myasthenic-patients, non-myasthenic patients and docking-time. Results: In myasthenic-patients the CLC cut-off value was settled at 19 patients. Considering the CLC cut-off of 19 patients, the whole series of myasthenic-patients was divided in two groups: phase 1 (first 19 cases) and phase 2 (last 51 cases).The mean operative time in phase 1 was 229,79±93,40 min while in phase 2 was 167,35±41,63 min, p<<0,001. In non-myasthenic patients the CLC cut-off value was at 16 cases. Again, the whole series was divided in two groups: phase 1 (first 16 cases) and phase 2 (last 27 cases). The mean operative time in phase 1 was 277, 44±90, 50 min while in phase 2 was 169, 63±61, 10 min, p=0,016. The LC for docking was overcome at 46 cases, recording a significant reduction of time after the first phase (28, 09±5, 37 min vs 19, 75±5,51 min, p<<0,001). The intraoperative and 30-day mortality were null in any phase of LC of myasthenic and non-myasthenic groups. There weren’t differences between the two phases of LC in terms of blood loss, duration of postoperative drainage, and postoperative stay in both myasthenic and non-myasthenic series. It was only recorded a significant higher hospital readmission at 30-days for myasthenic patients operated during the first phase (2 cases vs 0, p=0,02). Conclusions: According to our data, LC in RAT seems to be steep, and RAT confirms to be safe even before of CLC.